Brief explanations on EU Directive no. 680/27.04.2016 in the field of personal data processing - Mănescu, Dragoș Mihail (Technium Social Sciences Journal, 2021)
The processing of personal data is regulated by Directive 680/2016 when it is carried out by national security institutions or by law enforcement bodies. The Directive establishes the general framework for exemption from the principles of personal data protection enacted by the GDPR, establishing a restrictive and reasoned temporary derogation, considered indispensable for carrying out activities aimed at ensuring national security or the national judicial system, as well as prevention, detection and combating crime.